1995
DOI: 10.1002/1097-0142(19950315)75:6<1343::aid-cncr2820750617>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Second primary tumors in patients with head and neck squamous cell carcinoma

Abstract: Background. The concept that a patient could develop cancer twice was first put forward by Billroth. Second primary neoplasms are a particular feature of head and neck cancer. Methods. This study examines the records of 3436 patients with squamous cell carcinoma of the head and neck, of whom 274 subsequently developed a second neoplasm. Results. The actuarial second primary rate was 9.1% at 372 months, and median time to presentation for the second tumor was 36 months. Second tumors were more likely to occur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
198
2
15

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(234 citation statements)
references
References 43 publications
17
198
2
15
Order By: Relevance
“…The 3-year OS rate for patients with RIS in our series (32.4%) was within the lower end of the wide range reported previously (8%-60% at 5 years). [3][4][5][6][7][8][9][10][11][12][13]34 The best survival outcome was reported by Tabone et al, 35 who reported that the OS and eventfree survival rates for 23 patients with radiation-related osteosarcoma at 8 years were 50% and 41%, respectively.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
“…The 3-year OS rate for patients with RIS in our series (32.4%) was within the lower end of the wide range reported previously (8%-60% at 5 years). [3][4][5][6][7][8][9][10][11][12][13]34 The best survival outcome was reported by Tabone et al, 35 who reported that the OS and eventfree survival rates for 23 patients with radiation-related osteosarcoma at 8 years were 50% and 41%, respectively.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
“…Second cancers predominantly affect the head and neck area, oesophagus or the lung [1,2]. The prevalence of a second SCC in cadaver dissection studies ranges between 3.7% and 15.5% [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among HNSCC patients, the frequency of SPT occurrence ranges from 12 to 30% with a constant rate of 2-3% per year for patients who survive for more than 10 years. (1)(2)(3) The first tumor is responsible for 15% of patient deaths, whereas the second tumor is the cause of death in 71% of cases. Squamous cell carcinoma is the predominant histological type of the second tumor.…”
mentioning
confidence: 99%